A questão do mundo na fenomenologia de Edmund Husserl - Cabral, Michelle Silvestre (2010)
The goal of this dissertation is to investigate the statute of the notion of world in Husserl‟s phenomenology. It starts of an analysis of the elements involved in the characterization of this as universal objective correlate of the transcendental life. To do so, it was necessary to examine the notions of conscience and epoché, insofar as the understanding of its unique and original sense is determinative to a full apprehension of the proposed question. The notion of conscience is elaborated by Husserlian phenomenology in a radically opposing meaning to the modern conceptions of it, in which it was conceived, in general, as psychic interiority that articulates ideas or psychological data from incoming from stimulations received from the outside. According to Husserl, the true subjectivity should be described as ideal- transcendental field that encloses the constitution of both the poles involved in any experience. Its basic characteristic will be drawn by intentionality operative that ensure the direct correlation between possible subjects and possible objects. The method that allows to have access such field, becoming possible the pure description of the reference apriórica of the noetic acts its respective noematic correlates, is the method of epoché. The validation of this as appropriate procedure and demanded by the character of the inquiry is indispensable within the Husserlian thought. The process of eidetic variation and the role of the fantasy are also highlighted in function of its importance in the whole operation. The conception of the world drew from the use of this methodology that invalidates the natural attitude of consideration, while an naive and insufficient procedure to establish the knowledge, is extracted, first, in a movement of refutation to the concept modern of world. The conception of world as a horizon of meaning for each and every experience is based only through the overcoming of the traditional figures of conscience and idealism. The new meaning, established by phenomenology, brings as specificity determinative the essential character of the analysis, resource that allows it to raise it to the transcendental attitude of inquiry abandoning, concomitantly, the facticity imposed by natural consideration. The meticulous examination of the essential structure present in any one experience allows the verification of the horizons involved in each individual lived. The interconnection of these in an indefinite system of new experiences eidetically predetermined from the internal and external horizons of each objectivity individually taked, leads to the total horizon of the world. The world then will be characterized as the horizon of horizons or, still, as correlative infinite idea to infinities of possible experiences in the unity of one same life. It is, at last, to understand the world as sense Omni-encompassing that involves each individual experience in order to determine the indefinite possibility experiences possible according to the telos of agreement and sedimentation.